Un musée technique, d’histoire et de société : l’apport des collections iconographiques du musée de l’Air et de l’Espace - Clémence Raynaud (In Situ)
The French air and space museum at Le Bourget possesses over 400 aeroplanes and is generally considered as a technical museum. From the time of its creation, however, graphic documents and art objects were collected in an approach which aimed to take into account the historic and cultural aspects of the conquest of the air from the eighteenth century on. These collections now comprise some 24,400 items including paintings, engravings, posters, post cards, art objects, sculptures, toys and so on. The iconographical collections bring different approaches to the understanding of everything relating to aviation, from social, cultural, economic and anthropological point of view. The ‘technical’ label attached to the museum consequently seems to be very restrictive. But this restrictive view was nonetheless the one that prevailed for a long time, seeing the picture collections as of secondary importance and understanding the real aircraft as chapters in a presentation centred on the exploits of the great figures of aviation. New attention to the iconographical resources of the museum is one of the key features of the new presentation of flight prior to 1918 which will occupy the space of the 1937 air terminal building, which has been completely restored. Flying machines and their representations will enter into a kind of dialogue in a museum visit that will allow for a plurality of approaches, open to the phenomena and changes of which flight was both a vector and a mirror in contemporary history.